2017
DOI: 10.1002/jsfa.8756
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nano/micron vegetable carbon black on mechanical, barrier and anti‐photooxidation properties of fish gelatin film

Abstract: With improved properties, the nano VCB-reinforced GEL film may have great potential for application in the edible packaging field, especially for the anti-photooxidation property. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…These results are similar to Lee and Yoo, who studied large starch granules embedded in gelatin films and concluded that the large starch granules created numerous small voids for water molecules to permeate . At the same time, KRT is of a fibrous construction, thus this construction twined with the crosslinking collagen fiber, results in forming a number of tight structures barring water molecules from entering the structure, similar to results reported previously . Furthermore, crosslinking collagen fiber films with an increasing content of SPI, showed a decrease in the WVP value, this may be attributed to SPI readily interacting with amino groups via hydrogen‐bonding to form crosslinked networks preventing water molecules from penetrating the films .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These results are similar to Lee and Yoo, who studied large starch granules embedded in gelatin films and concluded that the large starch granules created numerous small voids for water molecules to permeate . At the same time, KRT is of a fibrous construction, thus this construction twined with the crosslinking collagen fiber, results in forming a number of tight structures barring water molecules from entering the structure, similar to results reported previously . Furthermore, crosslinking collagen fiber films with an increasing content of SPI, showed a decrease in the WVP value, this may be attributed to SPI readily interacting with amino groups via hydrogen‐bonding to form crosslinked networks preventing water molecules from penetrating the films .…”
Section: Resultssupporting
confidence: 90%
“…27 At the same time, KRT is of a fibrous construction, thus this construction twined with the crosslinking collagen fiber, results in forming a number of tight structures barring water molecules from entering the structure, similar to results reported previously. 28 Furthermore, crosslinking collagen fiber films with an increasing content of SPI, showed a decrease in the WVP value, this may be attributed to SPI readily interacting with amino groups via hydrogen-bonding to form crosslinked networks preventing water molecules from penetrating the films. 29 Therefore, the addition of the proteins could change the barrier properties of the crosslinked collagen fiber films, which will offer potential of regulating films as packaging material.…”
Section: Water Vapor Permeability (Wvp)mentioning
confidence: 99%
“…In the food industry, VC is primarily used for colouring and shading confectionery (Bechtold & Mussak, 2009;Lehto et al, 2017). Due to its ability to eliminate bacteria and toxins, VC is now being used in various products such as ice cream, sugar masses, creams and toppings for cakes and pastries, and gelatin films (Wrolstad & Culver, 2012;Ding et al, 2018). Food-grade VC is obtained through the carbonisation of plant raw materials and is crushed into a fine powder (EFSA, 2012;Houghton & Hendry, 2012).…”
Section: Introductionmentioning
confidence: 99%